Development and Application of the TPACK-P Education Program for Pre-Service Teachers’ TPACK - Won Kim, Seong; Lee, Youngjun; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study aimed to investigate and complement the ways of improving the Technological Pedagogical Content Knowledge-Programming (TPACK-P) educational program and verify the improved program’s effect on pre-service teachers’TPACK.Methods/Statistical Analysis: The TPACK-P educational program was conducted for 19 pre-service teachers; two difficulty items were investigated. A survey was administered to identify any improvement. To verify the effect of the improved program on the pre-service teachers’ TPACK, two programs involving distinct technological tools were applied to the control and experimental groups. To generate comparable results, the same research procedure was adopted as in a previous study, with some modifications.Findings: The pre-service teachers had difficulties in the process of learning programming, designing lessons, and developing programs in the TPACK-P educational program. In addition, they needed increased time for learning programming and analyzing the activities in the TPACK-P class. Therefore, the improved TPACK-P educational program added programming-based activities (analysis of curriculum based on programming, analysis of TPACK-P instructional cases, and development of the TPACK-P program in the programming environment). As a result of engaging the pre-service teachers in the improved TPACK-P educational program, the pre-service teachers’ TPACK was effectively developed in all areas. Moreover, it was found to be more effective in improving the knowledge of technology than information and communication technology (ICT)-based TPACK educational program was.Improvements/Applications: This study can be used as a basic foundation for carrying out programming-based TPACK education for pre-service teachers.